Ineffective Erythropoiesis in β-Thalassemia. (28th March 2013) - Ribeil, Jean-Antoine; Arlet, Jean-Benoit; Dussiot, Michael; Cruz Moura, Ivan; Courtois, Geneviève; Hermine, Olivier
Abstract : In humans, β -thalassemia dyserythropoiesis is characterized by expansion of early erythroid precursors and erythroid progenitors and then ineffective erythropoiesis. This ineffective erythropoiesis is defined as a suboptimal production of mature erythrocytes originating from a proliferating pool of immature erythroblasts. It is characterized by (1) accelerated erythroid differentiation, (2) maturation blockade at the polychromatophilic stage, and (3) death of erythroid precursors. Despite extensive knowledge of molecular defects causing β -thalassemia, less is known about the mechanisms responsible for ineffective erythropoiesis. In this paper, we will focus on the underlying mechanisms leading to premature death of thalassemic erythroid precursors in the bone marrow.